¡Vamos! Let's go to the market [book with audioplayer] - Raúl the Third, 1976- (Findaway World, LLC, 2020)
Little Lobo, a Mexican American, and Bernabe, his dog, deliver supplies to vendors at the Mercado, a busy border town market.